2019
DOI: 10.9779/pauefd.452646
|View full text |Cite
|
Sign up to set email alerts
|

2005’ten 2018’e Ortaokul Matematik Dersi Öğretim Programlarının Değerlendirilmesi

Abstract: Talim ve Terbiye Kurulu Başkanlığı (TTKB) tarafından yayınlanmış olan ortaokul matematik dersi öğretim programları belirlenen amaçlar (hedefler), içerik (öğrenme ve alt öğrenme alanları), hedeflenen yetkinlikler, kazanımlar, beceriler ve ders saatleri bütünüyle karşılaştırılarak incelenmiştir. Bu sebeple çalışmada, nitel analiz yöntemlerinden doküman incelenmesi tekniği tercih edilmiştir. Bu yöntem doğrultusunda çalışma; araştırma problemlerini belirleme, veri toplama, verileri değerlendirme, bulguları analiz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
(3 reference statements)
0
7
0
2
Order By: Relevance
“…The majority of the mathematics teachers defined the changes in the mathematics curriculum as a decrease in the number of outcomes and a displacement of the outcome statements. The number of outcomes in the mathematics course curriculum from 2005 to 2018 had been reduced and the minimum number of outcomes was included in the mathematics course curriculum for 2018 (Baş, 2017(Baş, , Şen, 2017İlhan and Aslaner, 2019). The Ministry of Education (2017) stated that curricula were prepared in a simple, understandable manner, with emphasis being placed on reducing the content density, considering innovations and developments in learning and teaching theories, the needs of the age, the expectations of the individual and society.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the mathematics teachers defined the changes in the mathematics curriculum as a decrease in the number of outcomes and a displacement of the outcome statements. The number of outcomes in the mathematics course curriculum from 2005 to 2018 had been reduced and the minimum number of outcomes was included in the mathematics course curriculum for 2018 (Baş, 2017(Baş, , Şen, 2017İlhan and Aslaner, 2019). The Ministry of Education (2017) stated that curricula were prepared in a simple, understandable manner, with emphasis being placed on reducing the content density, considering innovations and developments in learning and teaching theories, the needs of the age, the expectations of the individual and society.…”
Section: Resultsmentioning
confidence: 99%
“…Özcan and Delil, 2018), and comparison to the previous curricula (Baş, 2017;Şen, 2017;İlhan and Aslaner, 2019). However, only few of these studies evaluations were made using the Eisner Educational Criticism Model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are supportive statements about including the history of mathematics in the curricula of countries such as China, Germany, Poland, and Portugal (Fauvel & Maanen, 2002). Considering the new curriculums published in 2009, 2013, and 2018 (İlhan & Aslaner, 2019) by the Ministry of National Education in Turkey, which included constructivist approaches in its curriculum as of 2005, in the 2009 mathematics curriculum, it was stated that it was among the general aims of contributing to students" understanding of how mathematics developed in the historical process, what role it played in the development of human thought, and how it provided benefits to other sciences. The curriculum does not only mention the importance of the history of mathematics but also includes examples of activities for the history of many concepts such as probability, rational numbers, clock, money, geometric objects, and measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The new system necessitated a new English curriculum since students started to receive English teaching from the second grade onward instead of fourth grade (Özüdoğru, 2017). Besides, some revisions were made in aims, content, learning-teaching process and assessment and measurement dimensions of various curricula such as science teaching, mathematics and information technologies and software teaching (Deveci, 2018;İlhan & Aslaner, 2019;Karaman & Karaman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these research studies, no studies have been found specifically targeting on 2018 Turkish national curriculum change. However, it was reported in various studies that 2018 curricula experienced some important changes in aims, content, learning-teaching process and measurement and assessment dimensions such as increase in competencies and skills in mathematics curricula (İlhan & Aslaner, 2019) or removal of 'applied science' content in science teaching curricula (Başar & Demiral, 2020) and a new primary school curriculum was also developed for Information Technologies and Software course (MoNE, 2018). For these reasons, it is considered necessary to explore teachers' perception of new curricula.…”
Section: Introductionmentioning
confidence: 99%